METHODOLOGY OF USING MOTOR GAMES IN PHYSICAL EDUCATION OF CHILDREN OF SENIOR PRESCHOOL AGE WITH A FOCUS ON THE FORMATION OF SOCIAL ACTIVITY (Physical Culture and Sport: Scientific Perspective, 2025)
The purpose of our research: to develop and substantiate the methodology for using outdoor games in the physical education of preschool children with an emphasis on the formation of social activity. The meaning of the term "social activity" is an indicator that reflects the cognitive, emotional-motivational, behavioral aspect of the social activity of preschool children. The use of outdoor games in the educational process of preschool children is a priority and effective means of interaction potential for the formation of social activity of older preschool children.The methodology for using outdoor games in physical education of senior preschoolers with an emphasis on the formation of social activity will be pedagogically appropriate and effective if it is built on the basis of the use of five types of outdoor games (story-role-playing games, fun games, pantomime games, folk games, competitive games) with a gradual transition from the predominant use of collective games and team competitions to outdoor games, where the individual result is important, optimally combining group and individual forms of conducting classes in the organization of the educational process. The basis of programs aimed at preventing passive orientation in behavior and forming social activity are game forms of classes. One of the important areas that influence the formation of the personality of a preschooler is physical culture. Its role is unique in terms of the comprehensive development of all aspects of a holistic personality. Physical culture gradually prepares the child for inclusion in all the complexities of the system of social relations. This study presents a methodology for using outdoor games in the physical education of preschoolers with an emphasis on the development of social activity. The results of the analysis of the parameters of social activity, emotional-evaluative, cognitive and behavioral components were carried out. The level of physical fitness of children of senior preschool age was determined. The components that influence the formation of social activity of preschoolers in the process of education and upbringing are characterized.
Keywords: outdoor games; educational process; self-esteem; social relations; emotional-evaluative component